2005
DOI: 10.1007/s00392-005-0209-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac risk of coronary patients after reintegration into occupations with heavy physical exertion

Abstract: The job related reintegration of patients with coronary artery disease (CAD) is a central part of cardiac rehabilitation. However, specific occupational demands like jobs with heavy physical exertion (> 6 METs) could increase the cardiovascular risk because the relative risk for acute myocardial infarction (MI) and cardiac death is temporarily elevated after vigorous exertion ("hazard period"). Thus, in 2001 any male patient with proven CAD who performed a job with heavy exertion until the occurrence of an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Nevertheless when these subjects are symptomatic, a clear guidelines have not yet been defined and the treatment is still controversial. The finding, in our case, of posterior course of the LM without atherosclerotic lesions has proved crucial to determine the therapeutic treatment with only antihypertensive drugs and to allow the patient to re-entry into the workforce even with suggestion to reduce the effort under 6 METs (as the transport of weights above 15 kilos) and to avoiding work on overhead lines too, although the patient reported that he had never worked on power lines [20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless when these subjects are symptomatic, a clear guidelines have not yet been defined and the treatment is still controversial. The finding, in our case, of posterior course of the LM without atherosclerotic lesions has proved crucial to determine the therapeutic treatment with only antihypertensive drugs and to allow the patient to re-entry into the workforce even with suggestion to reduce the effort under 6 METs (as the transport of weights above 15 kilos) and to avoiding work on overhead lines too, although the patient reported that he had never worked on power lines [20,21]. …”
Section: Discussionmentioning
confidence: 99%